Control Mechanism and Value of Firm: Empirical Evidence from Indonesia Capital Market - Herdinata, Christian; Tandelilin, Eduardus; Hermeindito, Hermeindito (Universitas Prasetiya Mulya, 2013)
This research discusses about the roles of institutional ownership and leverage as control mechanism over agency conflict and how it affects corporate performance. Agency conflict is a result of expropriation via tunneling on asset utilization. This study uses panel data with a sample of 136 companies in Indonesia between 2001-2012. Simultaneous model testing using Three Stage Least Square estimation technique is also used in this study. Results suggest that institutional ownership and leverage have a non-linear effect on asset utilization. Institutional ownership can be used as a control mechanism at higher levels of ownership. However, when the ownership surpasses certain level, institutional owners will be able to conduct expropriation through tunneling. Low-level leverage will result in expropriation through tunneling by institutional owners. On the other hand, higher level of leverage makes it possible to use leverage as control mechanism. This study also suggests that there is a substitutional correlation between the implementation of control mechanism and leverage. This research also proves that the effect of control mechanism on asset utilization will improvecorporate performance. This research does not specifically investigate the proportions of institutional ownership and leverage as borderline threshold which shows that the two variables can be used as control mechanism. It also implies that the control mechanism over agency conflict which happens as a result of expropriation through tunneling can be done using institutional ownership and leverage. Institutional ownership and leverage must, in this case, be conducted properly towards asset utilization so that it can improve corporate performance. This research provides evidence and solutions for agency conflicts that happen as a result of expropriation through tunneling. This study also contributes to the agency theory testing model by using simultaneousequation and considering non-linear testing method.